CARLA BRISOTTO, FABIANO LEMES DE OLIVEIRA (eds.) - Re-Imagining Resilient Productive Landscapes: Perspectives from Planning History - Monclús Fraga, Javier (ZARCH, 2023)
Carla Brisotto, Fabiano Lemes de OliveiraRe-Imagining Resilient Productive Landscapes: Perspectives from Planning HistoryCham (Switzerland): Springer, 2022. 326 pp. Tapa dura. Idioma: inglés. 116,00 €ISBN: 978-3-030-90444-9